Village Head Leadership Optimization During COVID-19 Pandemic in Sula Regency: Study of Handling Direct Cash Funds in Falahu Village - Batjo, Sitti N.; Jaali, La (Devotion : Journal of Research and Community Service, 2023)
The Village Head has the position of Head of Village Government who is in charge of administering Village Government, carrying out development, community development, and community empowerment. The village head as the formal leader of the village acts as a motivator, facilitator and mediator who is very important for the success of each planned development program and plan. The purpose of study is to find out village head leadership optimization during COVID-19 pandemic in sula regency regarding study of handling direct cash funds in Falahu village. This research is a type of descriptive research with qualitative analysis which is a problem-solving procedure investigated by describing and describing the state of an object at the time of research based on the facts that appear as they are. This information is needed to find out the Optimization of Village Head Leadership in Handling Direct Cash Assistance Funds During the Covid-19 Pandemic in Falahu Village, Sanana District, Sula Islands Regency. Research data was collected either through data collection instruments, observation, interview guidelines, documentation. From the results of the research and discussion that has been carried out, it can be concluded that the leadership factor plays an important role because it is the leader who will move and direct the community in achieving goals and at the same time is a task that is not easy because you have to understand the behavior of each subordinate and the different people. In general, and as a whole has optimized his leadership role both starting from the role of responsibility, communication, interpersonal, informational and decision-making.